Wind Energy Potential Investigation and Micrositting in Langkawi Island, Malaysia. Issue 1 (February 2013) - Albani, A.; Ibrahim, M.Z.; Yong, K.H.; Muzathik, A.M.
The aim of this study was to predict the wind energy potential over the Langkawi Island, Malaysia. The wind data for year 2009 was collected from Malaysia Meteorology Department (MMD) and then extrapolated to the hub heights of various turbines. Wind turbines with rated powers between 1 kW and 110 kW were chosen for annual energy production calculations and best fitted ones were used for the micrositting analysis. In this study, the turbine with 22 kW rated power with hub height 30 m was selected based on its best value of capacity factor. The wind speed frequency per year is highly peaked in the range 1–6 m/s, this indicate that most of the wind speed at Langkawi Island lies in this range. The 'WAsP' and 'WindPRO' softwares were used for the wind statistics and energy calculations. Calculated energy production of located 10 turbines with total capacity of 0.22 MW was 111.1 MWh. Suitable sites were selected according to the created wind power and energy maps. The future cost of maintenance and the status of area either its reserved or conserved by the government were the factors that be considered for selection of site area.